Urban Voids in Gabii? Results of a Pilot GPR Survey - Andreotti, Chiara; Bochicchio, Rocco; Henke, Felix; Schreyer, Julian (Archäologischer Anzeiger, 2024)
In 2022, a small-scale GPR survey was conducted in the Gabii urban area in order to test the practicability of GPR at Gabii and to ›flesh out‹ the previously discovered street system with buildings. 4200 m² were therefore prospected east of the main road fork. Apart from a likely post-antique system of north-south running structures, the survey yielded a mostly negative result: in surprisingly close vicinity to the city centre a street grid had been laid out, but apparently no (substantial) buildings were ever constructed along these streets. Should this result be confirmed by further research, this part of Gabii seems to have been even more thinly settled than suggested by recent excavations. The frequent 1ˢᵗ century B.C. allusions to settlement decline could in this case largely be attributed to the misguided idea that the fame of ancient Gabii must have been reflected in the physical extension of the urban centre.